2023
DOI: 10.3389/fpain.2023.1146667
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to improve pain phenotyping in head and neck cancer patients

Abstract: Pain associated with head and neck cancer (HNC) is difficult to manage and reduces quality of life. It has been increasingly recognized that HNC patients exhibit a wide range of pain symptoms. Here we developed an orofacial pain assessment questionnaire and conducted a pilot study to improve pain phenotyping in HNC patients at the diagnosis. The questionnaire captures the following pain characteristics: pain intensity, location, quality, duration, and frequency; the impact of pain on daily activities; changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“… 51 , 52 A pilot study in Brazil found that HNC patients experience a wide range of pain symptoms with altered mechanical, chemical, and temperature sensation. 50 This may be a reason for decreased dietary and ONS intake of HNC patients with pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 51 , 52 A pilot study in Brazil found that HNC patients experience a wide range of pain symptoms with altered mechanical, chemical, and temperature sensation. 50 This may be a reason for decreased dietary and ONS intake of HNC patients with pain.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, patients with pain were less likely to have ONS energy intake ≥400 kcal/day than those without the symptom. Pain affects more than 70% of HNC survivors 50 . Chronic pain resulted from cancer or cancer treatments such as surgery, radiation, and chemotherapies or in combination, is particularly challenging as patients suffer from multiple oral complications such as orofacial pain, changes in taste, and oral dysfunction 51,52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer pain usually affects several dermatomes. Of note, oral cancer patients often experience severe pain at the site of cancer with new sensitivity to spicy food [ 123 ]. These patients are very sensitive to local capsaicin challenge [ 124 ], indicating increased TRPV1 expression and/or sensitization.…”
Section: Topical Capsaicin Patch For Chemotherapy-induced Peripheral ...mentioning
confidence: 99%